Precoding technique for optimum spectral efficiency in massive MIMO system / Muhammad Firdaus Hashim - Hashim, Muhammad Firdaus (2016)
Massive MIMO is used in a new generation wireless technology and a method to improve the spectral efficiency (SE) of communications systems. Nowadays, because of the users and applications that are always increasing day by day the improvement of wireless technology shall be in line according to demand. In this paper, precoding technique used to optimize spectral efficiency and the number of user as a function of the number of antenna with different interference condition are investigated. From the simulation, SE per cell for precoding technique and corresponding number of scheduled users K* can be seen. As the number of antenna at base station (BS), M increase the SE will increasing. The K* depends on the intercell interference condition strongly.